THE NEEDS FOR ENGLISH LANGUAGE FOR TOURISM COMMUNICATION AMONG PEOPLE IN CULTURAL TOURISM AT WAT THAT NOI NAKHON SI THAMMARAT PROVINCE - Songyoo, Rojjanant (Journal of MCU Nakhondhat, 2023)
This research article is intended 1) to study the tourism situation of cultural sites Wat That Noi, Nakhon Si Thammarat Province 2) to explore the need to use English for communication tourism of people in cultural communities, Wat That Noi Province Nakhon Si Thammarat Is a qualitative research that collects data by means of interviews from tourists, people in the community, agencies and organizations involved By using structured interviews that have passed precision quality checks By those who have expertise, consider the content and suitability of the language used in the research by checking the index. Consistency Data is analyzed through the theoretical concepts chosen for the study using a three - poster data validation process. To find the answer to the research and analyze the data using descriptive statistics, including the average percentage from the study found that 1) Measuring the least elements Nakhon Si Thammarat province is the tourist attraction is very high. Because it is a famous tourist destination There is a beautiful landscape Clean and safe. SHA standards are received each day. There are tourists who have faith to their father, like verbal rights. Come to travel a lot, especially during long holidays and holidays. All relevant sectors Both the public and private sectors Participate in management, with few weaknesses and problems/The obstacles that have a huge impact on the quota - 19 situation have resulted in very few or almost no tourists, especially foreign tourists. 2) People in the community have English skills for communication, at a low level There is a need to develop English communication skills, in terms of speaking about daily greetings, using video clips